Rethinking digital policy and blockchain solutions for seamless logistics between Ukraine and the European Union - Tymokha , Denys; Khoroshaіlo, Rostyslav (Pressing Problems of Public Administration, 2025)
This article examines the prospects and mechanisms for integrating state digital policy with tokenized blockchain solutions to create a seamless logistics space between Ukraine and the EU. The authors identify three critical issues hindering efficient cross-border movement of goods: inefficiencies in customs documentation and border crossing procedures, inadequacies in cross-border payment and settlement systems, and gaps in insurance coverage. The research demonstrates that implementing standardized blockchain solutions can significantly transform logistics operations between Ukraine and the EU, reducing customs clearance time by 80-90% and decreasing cross-border payment costs by 40-60%. Special attention is paid to innovative concepts of metadocuments, atomic transactions, and meta-assets, which form a new technological foundation for addressing key cross-border logistics challenges. Metadocuments integrate not only document content but also their procedural and legal context, ensuring self-verification and data integrity. Atomic transactions, implementing the «all-or-nothing» principle, eliminate risks of incomplete operations and reduce transaction costs. Meta-assets create opportunities for developing flexible insurance products through fragmentation and efficient risk distribution. The article substantiates that the digital transformation of logistics requires rethinking the very paradigm of public administration, creating a new type of «algorithmic governance.» The authors propose conceptual directions for integrating state regulatory policies in the field of digital logistics transformation and determine their potential impact on the efficiency of cross-border freight transportation in the long-term perspective up to 2045. According to forecasts, implementing the proposed measures could provide savings of up to €14 billion annually for cross-border trade between Ukraine and the EU, contributing to deeper economic integration and post-war recovery.